Metal-organic frameworks-derived CaO/ZnO composites as stable catalysts for biodiesel production from soybean oil at room temperature - Maryam Sharifi; Shahram Tangestaninejad; Majid Moghadam; Afsaneh Marandi; Valiollah Mirkhani; Iraj Mohammadpoor-Baltork; Sahar Aghayani (Scientific Reports)
Abstract Biodiesel presents a sustainable alternative to fossil fuels, yet traditional homogeneous catalysts like sodium and potassium hydroxide face challenges with separation and reuse. Calcium oxide (CaO) is an effective heterogeneous catalyst for biodiesel production, but its chemical instability under reaction conditions restricts its long-term performance. This study introduces MOF-mediated synthesis (MOFMS) of heterogeneous catalysts, specifically CaO@ZnO and ZnO@CaO nanocomposites, from inexpensive and non-toxic metal salts and linkers in water. Comprehensive characterization techniques, including XRD, FT-IR, BET, FE-SEM, ICP, and CO2-TPD, were employed to analyze these catalysts. When applied to biodiesel production from soybean oil at ambient temperature and pressure, CaO@ZnO and ZnO@CaO achieved impressive biodiesel conversion rates of 99% and 92%, respectively, within 25 min. Both catalysts maintained their activity over six utilization cycles, with Ca²⁺ leaching remaining below 4% (2% for CaO@ZnO and 4% for ZnO@CaO) after the sixth run. These results provide valuable insights into catalyst preparation and leaching control, enhancing reusability in biodiesel production. Future research should aim to improve the long-term stability and reusability of these catalysts, investigate their performance with various feedstocks, and evaluate the feasibility for industrial applications.